JUNIOR HIGH SCHOOL STUDENTS’ PERCEPTION ON THE USE OF GRAMMARLY ON WRITING TEXTS - Tiarma Intan Marpaung; Rosintan Yorini Siahaan; Lidia Zega; David Togi Hutahaean (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2023)
Writing skill is specific abilities which help writers put their thoughts into words in a meaningful form and mentally interact with the message. The objectives of this research to describe the students’ perceptions and the strength and the weakness of Grammarly. The research designed this study with qualitative method with the data from questionnaire. The findings show that: The use of Grammarly has been seen positively by students, with 80.1% strongly agree category. Grammarly has both strengths and weaknesses. Grammarly's strengths are that it provides both direct and indirect feedback, and that the feedback is simple to interpret. Grammarly also includes simple tools that can detect small mistakes in students' writing. Meanwhile, Grammarly's weaknesses include limited usage, the requirement to pay if students want to use all of Grammarly's premium features, and Grammarly's feedback was not always clear, requiring students to have a good understanding of grammar. Grammarly, on the other hand, has both advantages and disadvantages. The advantages of Grammarly are that it provides faster correction and that its features are simple to understand.